Deficit fear as a modulator of disbelief in the framework of self-perception among students at the stage of self-isolation - M. M. Basimov (Вестник университета)
The article examines how deficit fear affects the formation of the actual self-perception of “believer” among students during the period of self-isolation (Covid-19 pandemic). The deficit fear in the causal picture was determined as the reason influencing the dynamics of the actual self-perception of the “Unbeliever-believer”. To analyze statistical relationships, the author’s method was used, based on a general comparison of all quantile data partitions for each studied parameter. This dependence is represented as an asymmetric oscillation when the correlation is very weak and not even significant. It demonstrates one of the two main types of errors in the interpretation of the results of correlation analysis, which are ignored in the psychological community. A detailed psychological interpretation of the revealed connection shows how dangerous it is, especially when using the results in practice, to remain within the framework of linear representations when considering complex psychological phenomena and processes. In addition, three graphs of the dependencies of the indicator of the actual self–perception “Unbeliever – believer” on three indicators of fear (constructive, deficit and destructive) are clearly analyzed, when all the connections within the correlation analysis are extremely weak, but with a nonlinear approach, one of the three dependencies is strong as the simplest nonlinear.